2017
DOI: 10.1007/s10597-017-0147-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Community-Based Frailty Intervention Among Middle-Aged and Older Prefrail and Frail Homeless Women: A Pilot Randomized Controlled Trial

Abstract: Interventions are needed to address frailty and other behaviors (e.g., drug and alcohol use) among prefrail and frail homeless women (P/FHW). The purpose of this pilot randomized controlled trial (RCT) was to compare the efficacy of a Frailty Intervention (FI) versus a Health Promotion (HP) program among P/FHW (N=32). Structured instruments assessed sociodemographics, individual, situational, health-related, and behavioral factors. While program differences were not statistically significant with the main outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…The therapy aimed at improving cognitive skills, such as attention, memory, speed of processing and reasoning, and problem solving. The frailty intervention used by Salem et al () aimed to address the physical, psychological and social frailty of homeless women and consisted of six group sessions for health promotion education and nurse case management. Shern et al () used the psychiatric rehabilitation model for homeless persons with severe psychiatric disabilities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The therapy aimed at improving cognitive skills, such as attention, memory, speed of processing and reasoning, and problem solving. The frailty intervention used by Salem et al () aimed to address the physical, psychological and social frailty of homeless women and consisted of six group sessions for health promotion education and nurse case management. Shern et al () used the psychiatric rehabilitation model for homeless persons with severe psychiatric disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported an adequate method of blinding of participants and personnel and six studies clearly stated blinding of outcome assessors. Attrition bias was low in 13 studies for the following reasons: six studies reported results of intention‐to‐treat analyses (Chang et al, ; Garland et al, ; Guo et al, ; Krabbenborg et al, ; Reback et al, ; Shern et al, ); four studies reported that missing outcome data were unlikely to be related to true outcomes (Himle et al, ; Malte et al, ; Medalia et al, ; Salem et al, ); two studies imputed missing data using appropriate statistical methods (Lester et al, ; Toro et al, ) and missing outcome data were balanced in numbers across groups in one study (Upshur et al, ). Low risk of bias in selective reporting was observed in 11 studies, which reported all expected outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…45 Based on our most recent qualitative findings in Prakasam and in consideration of our previous research findings, it is critical to incorporate both nurses and community health workers (CHWs) or ASHA to deliver the intervention taking into account the family unit, along with providing food supplementation, the provision of emotional support, and assistance with transportation and health care access. Previous research has utilized a combination of nurses and CHWs in the provision of health services 56,57 ; this cost-effective model can be applied and tailored in a culturally sensitive manner to rural WLHA. The purpose of using this model is to provide self-management support utilizing a health care provider and CHW equivalent, namely ASHA.…”
Section: Nurse-led Program Development Implicationsmentioning
confidence: 99%